Cerai Talak di Kota Palopo (Faktor Penyebab dan Solusinga dalam Studi Kasus di Pengadilan Agama) - Muhammad Tahmid Nur (Palita: Journal of Social Religion Research, 2016)
Marriage is one of the manifestations of human nature in the world to find happines, and make their descendant. Unfortunately, not all marriages are lasting until the end of the age, and not a litle ended in divorce. one case of divorce, is when a husband on his wife filed for divorce in religious courts. It dilator overshadow the many factors causing the disharmony that leads todivorce. However, the judiciary and the associated constantly seek and forge solutions to minimize the number of divorce cases divorce tends to increase from year to year.